2022
DOI: 10.3390/ijerph20010377
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Burnout and Engagement after COVID-19 among Psychology and Nursing Students in Spain: A Cohort Study

Abstract: The COVID pandemic has 0drastically changed the functioning of universities in Spain and may have altered individuals’ behaviours and emotions, the way they engage in the learning process and their psychological well-being. Burnout syndrome is a psychological problem that arises from persistent confrontation with emotional and interpersonal stressors. COVID-related burnout among Spanish students has received little research attention. For this study, a pre-post cohort study design was used. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“…Por lo tanto, es fundamental contar con instrumentos validados para medir la Obsesión por el Estudio en otros idiomas para llevar a cabo estudios transculturales. Por ello, el presente estudio tiene como objetivo validar las escalas de Obsesión por el Estudio en estudiantes universitarios españoles, en los que las variables relacionadas con el estudio — incluyendo el agotamiento ( burnout ) académico y la implicación con el estudio — se han estudiado cada vez más en los últimos años (por ejemplo, Capdevila-Gaudens et al, 2021; Carbonell et al, 2023; Gil-Calderón et al, 2021; Martínez-Rubio et al, 2020; Morales-Rodríguez et al, 2020; Raimundo et al, 2023; Rodríguez-González et al, 2023). Asimismo, analizar la Obsesión por el Estudio en España es de suma importancia ya que la tasa de abandono es elevada en los universitarios españoles — en los estudiantes italianos la Obsesión por el Estudio predice positivamente la tasa de abandono (evaluada más específicamente como intención de abandono; Loscalzo, 2021; Loscalzo & Giannini, 2019).…”
Section: Alta Inversión En El Estudio En Estudiantes Universitarios E...unclassified
See 1 more Smart Citation
“…Por lo tanto, es fundamental contar con instrumentos validados para medir la Obsesión por el Estudio en otros idiomas para llevar a cabo estudios transculturales. Por ello, el presente estudio tiene como objetivo validar las escalas de Obsesión por el Estudio en estudiantes universitarios españoles, en los que las variables relacionadas con el estudio — incluyendo el agotamiento ( burnout ) académico y la implicación con el estudio — se han estudiado cada vez más en los últimos años (por ejemplo, Capdevila-Gaudens et al, 2021; Carbonell et al, 2023; Gil-Calderón et al, 2021; Martínez-Rubio et al, 2020; Morales-Rodríguez et al, 2020; Raimundo et al, 2023; Rodríguez-González et al, 2023). Asimismo, analizar la Obsesión por el Estudio en España es de suma importancia ya que la tasa de abandono es elevada en los universitarios españoles — en los estudiantes italianos la Obsesión por el Estudio predice positivamente la tasa de abandono (evaluada más específicamente como intención de abandono; Loscalzo, 2021; Loscalzo & Giannini, 2019).…”
Section: Alta Inversión En El Estudio En Estudiantes Universitarios E...unclassified
“…Therefore, it is critical to have validated instruments to measure Studyholism in other languages to conduct cross-cultural studies. Hence, the current study aims to validate Studyholism scales on Spanish college students, where academic-related variables — including academic burnout and study engagement — have been increasingly studied in recent years (e.g., Capdevila-Gaudens et al, 2021; Carbonell et al, 2023; Gil-Calderón et al, 2021; Martínez-Rubio et al, 2020; Morales-Rodríguez et al, 2020; Raimundo et al, 2023; Rodríguez-González et al, 2023). Also, analysing Studyholism in Spain is of foremost importance since the dropout rate — which in Italian students (more specifically evaluated as dropout intention) is positively predicted by Studyholism (Loscalzo, 2021; Loscalzo & Giannini, 2019) — is high in Spanish college students.…”
mentioning
confidence: 99%
“…The transition from traditional to online teaching and then back to traditional teaching enhanced anxiety and burnout in all actors involved in the educational process (de la Fuente et al, 2021;Salmela-Aro et al, 2022;Sengupta and Blessinger, 2021). Research following the pandemic period identified high levels of burnout among students, especially exhaustion and cynicism (Aguayo-Estremera et al, 2023), highlighted by the experienced demands (e.g. workload, changes in teaching and assessment methods, lack of direct interactions with colleagues and so on).…”
Section: Introductionmentioning
confidence: 99%
“…workload, changes in teaching and assessment methods, lack of direct interactions with colleagues and so on). If these requirements were perceived as exceeding personal resources to manage them, they became a stressful factor that favored the occurrence of burnout (Aguayo-Estremera et al, 2023;Lacombe et al, 2023). Thus, overwhelmed by all these transformations, students experienced exhaustion from the new academic requirements, combined with a "cynical and detached attitude towards study" (Schaufeli et al, 2002, p. 73).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation